Asuhan Kebidanan Continuity of Care (CoC) pada Ny. E Umur 30 Tahun di PMB Subiyatun, S.St.Keb - Subiyatun; Yulia Nur Khayati (Universitas Ngudi Waluyo, 2024)
Continuity of care in midwifery is a series of continuous and comprehensive service activities starting from pregnancy, childbirth, postpartum, newborn care and family planning services that connect the health needs of women in particular and the personal circumstances of each individual. Pregnancy care prioritizes continuity. The research design used is descriptive, with a case study approach (Case Study) with Varney Management and documented with SOAP. The case study was conducted on Mrs. E G2P1A0 in June to September 2024, the data collection method used interviews, observations with primary and secondary data through the KIA Book. Comprehensive midwifery care for pregnant women was found that the mother experienced complaints of discomfort in the third trimester and was managed by providing health education, normal delivery, the mother gave birth at 39 weeks of pregnancy at Gondo Suwarno Hospital. The newborn was normal and IMD was carried out. The mother's postpartum was normal and care was carried out according to the standard of care, namely 4 visits. The mother chose to use 3-month injection contraception. Comprehensive midwifery care will improve the health and well-being of the mother and fetus. Abstrak Continuity of care dalam kebidanan adalah serangkaian kegiatan pelayanan yang berkelanjutan dan menyeluruh mulai dari kehamilan, persalinan, nifas, pelayananbayi baru lahir serta pelayanan keluarga berencana yang menghubungkan kebutuhan kesehatan perempuan khususnyadan keadaan pribadi setiap individu. Asuhan kehamilan mengutamakan kesinambungan. Desain penelitian yang digunakan yaitu deskriptif, dengan pendekatan studi kasus (Case Study) dengan Manajemen Varney dan didokumentasikan dengan SOAP. Studi kasus dilakukan pada Ny.E G2P1A0 pada bulan Juni sampai September 2024 metode pengumpulan data menggunakan wawancara, observasi dengan data primer dan sekunder melalui Buku KIA. Asuhan kebidanan Komprehensif dari Ibu Hamil didapatkan ibu mengalami keluhan ketidaknyamanan pada kehamilan TM III dan ditatalaksana dengan pemberian Pendidikan kesehatan, Bersalin normal ibu bersalin pada umur kehamilan 39 minggu di RSUD Gondo Suwarno. Bayi Baru lahir normal dan dilakukan IMD. Nifas ibu normal dan dilakukan asuhan sesuai standa asuhan yaitu 4 kali kunjungan. Ibu memilih untuk ber KB Suntik 3 bulan. Dengan Asuhan kebidanan komprehensif akan meningkatkan kesehatan dan kesejahteraan ibu dan janin.